Praktikalitas Perangkat Pembelajaran Transformasi Geometri Berbasis Flipped Classroom Pada Peserta Didik Kelas XI SMAN 1 Padang - Desmaniati, Elsa; Fitriza, Rozi (Math Educa Journal, 2019)
This paper discuss about practicality of product that are result of developmental research of learning device based on flipped classroom to improve mathematical problem solving ability for XI grade students of Senior High School on transformation material. This developmental research using Tjeerd Plomp model development procedure consisting of 3 stages, namely preliminary analysis stage, prototype development stage, and assessment phase. Data of practicality are collected by observation sheets, interview and students quosionare. The result show that learning device (lesson plan, learning video, student work sheet) are practically on learning geometry transformation based on flipped classroom. Keyword: practicality, learning device of geometry transformation, flipped classroom